2004
DOI: 10.1038/sj.hdy.6800489
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite DNA variation reveals high gene flow and panmictic populations in the Adriatic shared stocks of the European squid and cuttlefish (Cephalopoda)

Abstract: 5 FAO-AdriaMed, Termoli (CB), ItalyIn the semienclosed Adriatic Sea, the shared stocks of the cephalopods Loligo vulgaris and Sepia officinalis represent important marine fisheries resources exploited by all coastal countries. The improving of knowledge on the demographic features of these shared stocks is internationally relevant for adopting responsible management and conservation of these marine resources. Analyses of microsatellite variation in geographical samples collected from all parts of the Adriatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 32 publications
7
29
2
1
Order By: Relevance
“…When loci Sof3 and Sof5 were excluded for the three northern sampling sites of the present study, a rather low mean number of alleles (N a = 6.9) was found that was comparable to the findings of Garoia et al (2004), who reported a mean number of 6.4 alleles per locus for the panmictic Adriatic cuttlefish.…”
Section: Within-sample Genetic Variabilitysupporting
confidence: 74%
See 4 more Smart Citations
“…When loci Sof3 and Sof5 were excluded for the three northern sampling sites of the present study, a rather low mean number of alleles (N a = 6.9) was found that was comparable to the findings of Garoia et al (2004), who reported a mean number of 6.4 alleles per locus for the panmictic Adriatic cuttlefish.…”
Section: Within-sample Genetic Variabilitysupporting
confidence: 74%
“…Locus Sof3 has been reported to display two parallel arrays of alleles differing by one base pair (Shaw and Pérez-Losada, 1999) and was omitted in the study of Garoia et al (2004). A biallelic character of Sof3 was also revealed in the current study; therefore, the sequences of several Sof3 clones were determined to reveal the nature of the differences prior to adjustment and binning of the two arrays (cf.…”
Section: Data Conversionmentioning
confidence: 99%
See 3 more Smart Citations